Updating the Training Subbranch of the Translation Studies Map - Li, Xiangdong (TRANS: Revista de Traductología, 2025)
The translation studies (TS) map (also known as the Holmes/Toury map) was conceptualized by Holmes (1972/1988) and visually presented to the TS community by Toury (1995). Over the past decades, the map has undergone updates to better represent the recent multidisciplinary development of TS. Despite acknowledgement of its value, for example, as an overall framework of the TS discipline, it has also been criticized for being close-ended and prescriptive. This article, based on a descriptive survey of 68 years of research in the field, aims to update the training subbranch of the TS map. The updated subbranch includes six clusters of areas, specifically, curriculum development and assessment, teacher, students, market and graduation, surrounding issues, and others. Hopefully, the enriched subbranch can provide scholars with a research context to identify research gaps and serve as a didactic tool in educating translators and novice researchers.